Researching with Proximity (Springer Nature, 2023)
This open access book presents a series of speculative, experimental modes of inquiry in the present times of environmental damage that have come to be known as the age of the Anthropocene. Throughout the book authors develop more nuanced ways of engaging with the environmentally vulnerable Arctic. They counter distancing, exoticising, and even apocalyptic imaginaries of the Arctic by staying proximate with mundane places and beings of the north. The volume engages and plays with familiar tourism concepts, such as hospitality, visiting, difference, care, openness, and distance, while expanding the focus from binary and human-centric approaches of hosts and guests to questions of wellbeing among multispecies communities. The transdisciplinary group of contributors share a curiosity about how staying proximate may provide theoretical depth and epistemological openings to attend to current tensions and to diversify the ways we do and enact research. Thus, each chapter provides a methodological experiment with proximity, developing diverse ways of envisioning and storying more-than-human worlds.